Performing Girlhood and Sisterhood in China: Chinese International Student Influencers’ Everyday Self-Presentation on RedNote - Wenxiang Zeng (Social Media + Society)
As young people begin to enact their agency and autonomy to share moments of everyday adolescence online, it can be challenging for them to strategically navigate the complicated digital sphere and maintain their digital fame and persona. This study investigates how adolescent Chinese international student lifestyle bloggers/vloggers become conspicuous influencers on the Chinese social media platform RedNote, through the performance of desirable girlhood and authentic sisterhood. The performance of girlhood is grounded in presentations of family love and care, an accomplishment of youth autonomy and competence, and a nuanced mixture of Chineseness and cosmopolitanism. The performed sisterhood is polished to be authentic thanks to well-curated amateur aesthetics, an approachable persona, and reciprocal female sistership. Their careful performances help them negotiate the tensions concerning age, class, gender, and nationhood in China’s social media entertainment ecosystem.